(untitled) (American Journal of Business Management, Economics and Banking, 2025)
The article theoretically substantiates the necessity and interrelation of accounting and internal control in budgetary organizations of the road sector. The legal bases of the organization of accounting and internal control in budgetary organizations are studied. Important directions of ensuring internal control through the organization and maintenance of accounting in budgetary organizations of the road sector are revealed. Proposals for improving internal control through the organization and maintenance of accounting in budgetary organizations are formulated.